Development of a hybrid LTS-HTS solenoid magnet for future intense muon beam lines - Kuno, Y; Shimonosono, T; Yokoi, T; Shimada, K; Sumiyoshi, Y; Yamamoto, A (2001)
A hybrid RandD magnet for future Phase Rotation Intense Secondary Meson (PRISM) beam project was designed and fabricated. The RandD solenoid magnet, which consists of an inner HTS coil and outer LTS coils, provides a central magnetic field of 10.6T at 90A in a warm bore diameter of 40 mm. The inner HTS coil was made by solenoid-winding technique without degradation of the BSCCO tapes. The RandD magnet was successfully cooled bg using cyrocoolers, and was stably operated at the design central field and was tested up to the maximum central field of 11.6T.